2015
DOI: 10.1002/er.3479
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of parabolic dish and parabolic trough solar thermal power plant using nanofluids and molten salts

Abstract: SUMMARYThe present study has been conducted using nanofluids and molten salts for energy and exergy analyses of two types of solar collectors incorporated with the steam power plant. Parabolic dish (PD) and parabolic trough (PT) solar collectors are used to harness solar energy using four different solar absorption fluids. The absorption fluids used are aluminum oxide (Al 2 O 3 ) and ferric oxide (Fe 2 O 3 )-based nanofluids and LiCl-RbCl and NaNO 3 -KNO 3 molten salts. Parametric study is carried out to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Selection of the most suitable collector type is dictated by the inlet temperature, and the findings in the literature are: (a) at applications of up to 100 o C, flat plate collectors are used [11]; (b) between 100 o C and 200 o C, evacuated collectors and collectors with low concentration ratios are used (<5) [12]; and (c) above 200 o C, parabolic trough collectors are used [13]. Abid et al [14] compared a solar dish collector with a parabolic trough collector and showed that the dish technology performs better energetically and exergetically. The main reason for this result is that higher concentration ratios are associated with lower thermal losses and higher thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of the most suitable collector type is dictated by the inlet temperature, and the findings in the literature are: (a) at applications of up to 100 o C, flat plate collectors are used [11]; (b) between 100 o C and 200 o C, evacuated collectors and collectors with low concentration ratios are used (<5) [12]; and (c) above 200 o C, parabolic trough collectors are used [13]. Abid et al [14] compared a solar dish collector with a parabolic trough collector and showed that the dish technology performs better energetically and exergetically. The main reason for this result is that higher concentration ratios are associated with lower thermal losses and higher thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Cingarapu et al [17] (on tin-based nanofluids for solar pumping designs), Ravindran [18] (on nano-fuels for rocket propulsion and solar power), Abid et al [19] (on salt-based ionic nanofluids for parabolic collectors) and Alashkar and Gadalla [20] (focused on gold and zinc oxide nanofluids for solar power pumps). All these studies confirmed the considerable elevation in thermal efficiency and sustainability of solar power designs attained with judicious deployment of metallic nano-particles.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid structures of wind and solar farms are the two most typical examples of this novel concept . However, this concept is only feasible when the existed power plant is located in a place where high potential of utilizing renewable energies such as solar or wind energy is available . In this hybridization program, solar energy can be utilized in several ways, eg, supplying the part of the required load by photovoltaic panels or contributing in the structure of the power plant as a heating source to provide the needed thermal energy …”
Section: Introductionmentioning
confidence: 99%